“Tupyje, dikije, idioty” vs. new theatre in Russia since the 1990s - Osińska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
In the Russian theatre, especially the postmodern one, since the turn of the 80s and 90s we have been able to observe that young theatre creators tend to adopt a defiant derisive attitude – both towards reality and to texts originating from the culture of the past which often constitute the subject matter of their works. A part of phenomena that are mentioned here might be presumably called ‘performances of laughter’ (as opposed to ‘performances of violence’ – this was the way the so-called new Russian drama was named by Mark Lipovetsky and Birgit Beaumers). This kind of artistic gesture was a reaction to the fact that in the former Soviet Union art was regarded as a mission and theatre was treated as a cradle of culture. They also meant a rebellion against authority figures, also the authority of tradition, and on the other hand they were an expression of surrender in the face of challenges brought in by the new social, political and cultural situation. In the article I assume that ‘performance of laughter’ and other theatre forms, whose authors undermined the possibility of rational cognition, simultaneously enhancing such strategies as absurd, eccentricity, chaos, infantilism, showing-off (in Russian „stiob”), originated from the chronologically earlier trend of visual arts, deriving from the Moscow Conceptualism. Therefore, I begin the article presenting the contents of the magazine “Hudozhestvennyi zhurnal” (2000, 26–27) dedicated to art taming the type of consciousness which medicine diagnoses as “idiotism”.